2019
DOI: 10.1149/2.1041914jes
|View full text |Cite
|
Sign up to set email alerts
|

Aprotic and Protic Ionic Liquids Combined with Olive Pits Derived Hard Carbon for Potassium-Ion Batteries

Abstract: In this work we report the use of the aprotic ionic liquid (AIL) 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr 14 TFSI) and the protic ionic liquid (PIL) 1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr H4 TFSI) in view of the realization of potassium ion batteries. Physicochemical characterization of electrolytes reveals features comparable to those obtained for lithium and sodium ion technologies. Electrochemical performance is evaluated in combination with olive pits deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…In addition, 0.5 m KTFSI/Pyr 14 TFSI was also compared with an protic ionic liquid, 0.5 m KTFSI/1‐butylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr H4 TFSI) when applied on olive pits derived hard carbon anodes in PIBs. [ 117 ] In spite of the similar conductivities and viscosities of these two ionic liquid electrolytes, a reversible K + insertion/deinsertion behavior is only demonstrated for Pyr 14 TFSI. By contrast, K + ions cannot be inserted and deinserted in hard carbon with Pyr H4 TFSI electrolyte due to the decomposition of Pyr H4 + cations, which leads to an unstable interphase.…”
Section: Electrolytes In Pibsmentioning
confidence: 99%
“…In addition, 0.5 m KTFSI/Pyr 14 TFSI was also compared with an protic ionic liquid, 0.5 m KTFSI/1‐butylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr H4 TFSI) when applied on olive pits derived hard carbon anodes in PIBs. [ 117 ] In spite of the similar conductivities and viscosities of these two ionic liquid electrolytes, a reversible K + insertion/deinsertion behavior is only demonstrated for Pyr 14 TFSI. By contrast, K + ions cannot be inserted and deinserted in hard carbon with Pyr H4 TFSI electrolyte due to the decomposition of Pyr H4 + cations, which leads to an unstable interphase.…”
Section: Electrolytes In Pibsmentioning
confidence: 99%
“…Using the same electrolyte, Masese et al. assembled a cell and evaluated the cyclic performance and rate capability of honeycomb‐structured layered K 2 Ni 2 TeO 6 and P2‐type K 2/3 Ni 1/3 Co 1/3 Te 1/3 O 2 [90] . The layered cathode materials in IL exhibited a stable charge‐discharge cycles even up to a high potential of 4 V vs .…”
Section: Ionic Liquid (Il) Electrolytes For Pibsmentioning
confidence: 99%
“…The physicochemical properties of the ionic liquid reported were comparable to the Na and Li ion technology. [203] Dias et al, carried out the molecular dynamics simulations of 1-ethyl-3-methylimidazolium tetracyanoborate ([EMIM] + [B(CN) 4 ] − ) ionic liquid to find out the influence of Na + /K + [B(CN) 4 ] − salts and poly(ethylene oxide) on transportation mechanisms. This study revealed that this ionic liquid mixture is a promising electrolyte for both SIB and KIB technologies.…”
Section: Ionic Electrolytesmentioning
confidence: 99%
“…Ajuria et al reported the performances of KIBs in aprotic ionic liquid (1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide [Pyr 14 TFSI]) and the protic ionic liquid (1‐butylpyrrolidinium bis(trifluoromethanesulfonyl)imide [Pyr H4 TFSI]), where hard carbon as used as electrode material. The physicochemical properties of the ionic liquid reported were comparable to the Na and Li ion technology . Dias et al, carried out the molecular dynamics simulations of 1‐ethyl‐3‐methylimidazolium tetracyanoborate ([EMIM] + [B(CN) 4 ] − ) ionic liquid to find out the influence of Na + /K + [B(CN) 4 ] − salts and poly(ethylene oxide) on transportation mechanisms.…”
Section: Different Electrolytesmentioning
confidence: 99%